1995
DOI: 10.1128/jb.177.3.596-607.1995
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of the Pseudomonas lemoignei polyhydroxyalkanoate depolymerase system

Abstract: Two types of C-terminal sequences apparently represent substrate-binding sites; the PHB type is present in the PHB depolymerases of A. faecalis and P. pickettii and in PhaZ2, PhaZ3, and PhaZ5, and the PHV type is present in the PHV-hydrolyzing depolymerases (PhaZ4 and PhaZ1). phaZ1 was transferred to A. eutrophus H16 and JMP222. All transconjugants of both strains were able to grow with extracellular PHB as a carbon source and produced translucent halos on PHB-containing solid media. PhaZ1, PhaZ2, PhaZ4, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 63 publications
3
96
1
4
Order By: Relevance
“…This led to the suggestion that the N. aegyptia PHB depolymerase is constitutive. Our results are in contrast to all other known PHB bacterial depolymerases, which are repressed in the presence of a soluble carbon source (Jendrossek et al, 1995). In accordance with our results are those reported for Pseudomonas lemoignei (Nakayama et al, 1985;Steinbüchel and Hein, 2001;Tomasi et al, 1996), which produced polymerase maximally during growth on succinate.…”
Section: Discussioncontrasting
confidence: 51%
“…This led to the suggestion that the N. aegyptia PHB depolymerase is constitutive. Our results are in contrast to all other known PHB bacterial depolymerases, which are repressed in the presence of a soluble carbon source (Jendrossek et al, 1995). In accordance with our results are those reported for Pseudomonas lemoignei (Nakayama et al, 1985;Steinbüchel and Hein, 2001;Tomasi et al, 1996), which produced polymerase maximally during growth on succinate.…”
Section: Discussioncontrasting
confidence: 51%
“…Whereas most PHA-degrading bacteria analyzed so far apparently produced only one PHA depolymerase, Pseudomonas lemoignei was found to have at least five PHA depolymerases (199). The structural genes of several PHA depolymerases have been cloned and sequenced (197,(200)(201)(202). Biochemical analysis of the purified depolymerase proteins and analysis of the DNA-deduced amino acid sequences revealed that PHA depolymerases apparently possess a catalytic triad consisting of serine, histidine and aspartate residues which have been demonstrated to form the active site in bacterial lipases (203).…”
Section: Biodegradability Of Phamentioning
confidence: 99%
“…The amino acid sequences of the OPHs from strain 113P3 and strain VM15C were aligned by CLUSTAL W (Thompson et al, 1994) with the hypothetical PHB depolymerases from Mesorhizobium loti, Rhizobium sp. and Sinorhizobium meliloti strain 1021, to which the OPH from strain 113P3 showed homology (29-32 % identity) and the well-characterized PHB depolymerases from Pseudomonas lemoignei (PhaZ1 to PhaZ5; Jendrossek et al, 1995b) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%